2011
DOI: 10.1179/026708310x12688283410325
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of accelerated creep rate on carbide particle distribution in martensite for 0·18C–11·5Cr–0·29V steel

Abstract: The number of carbide particles stringers at boundaries and subboundaries of martensite per unit of surface decreases with the third root of tempering time at 1073 K. The accelerated creep rate at 853 K depends on the number of stringers of carbide particles per unit of surface, and below an inflection point, the creep rate increases strongly. Equations relating for creep rate are discussed in terms of experimental creep rate, number of carbide particles stringers and average particles spacing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…By decrease in the number of stringers of particles below a critical level, the creep rate increases about four times by much smaller increase in particles size. 23 Therefore, it is justified to conclude that the greater creep rate at higher temperature is due also to factors unrelated to the creep mechanism affecting significantly the results of calculation of creep activation energy and stress exponent. If in these calculations the change of microstructure is neglected, only apparent values of both parameters are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…By decrease in the number of stringers of particles below a critical level, the creep rate increases about four times by much smaller increase in particles size. 23 Therefore, it is justified to conclude that the greater creep rate at higher temperature is due also to factors unrelated to the creep mechanism affecting significantly the results of calculation of creep activation energy and stress exponent. If in these calculations the change of microstructure is neglected, only apparent values of both parameters are obtained.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve a better fit of experimental and calculated creep rates 19–22 and a better fit of creep and α ‐iron volume diffusion activation energy 23, several earlier studies proposed the modification of Equation (3) with the introduction of a threshold stress ( σ ‐ σ th ) as well as of a rationalisation stress over shear modulus ( σ /G) or over yield stress at creep temperature ( σ / σ E ); moreover, the use of a stress exponent n >2 was suggested. A recent investigation of the effect of changes in the distribution of carbide particles in tempered martensite 13 showed that with the stress exponent n = 2 a better agreement was obtained between the experimental creep rate and the creep rate calculated from equation (3), while the following relation was used to deduce the particles spacing: With λ a – average carbide particles spacing, d – average particle size, f – volume share of carbide compounds 17.…”
Section: Resultsmentioning
confidence: 99%
“…All these equations do not include parameters related to the steel microstructure. In the equations developed on the base of the detachment approach to creep rate and creep activation energy, the particles size is considered 19, 26, 27, however, the difference between the results of calculations and of experimental creep rate is very great 13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In calculations of coarsening rate, it was assumed that the distribution of carbide particles was uniform and dependent of volume diffusion rate of chromium, element in substitution solid solution in ferrite, and the basic carbide‐forming element. The coarsening of particles at grain boundary was omitted, as in the examined steel the number of intra‐granular particles was much greater and the rate of decrease of the number of grain boundary particles stringers was much greater than particles growth …”
Section: Introductionmentioning
confidence: 99%